HUBUNGAN SANITASI LINGKUNGAN DENGAN KEJADIAN TB PARU DI DUSUN TAWANGSARI DESA BANDARSARIKECAMATAN NGORO KABUPATEN MOJOKERTO - Nur Hidayati, Rina; Andre Pramudya, Reza (JURNAL KEPERAWATAN SEHAT, 2016)
Tuberculosis or often called with pulmonary TB is a contagious infection caused by the bacteria mycobacterium tuberculosis. Pulmonary TB is a public health problem that arises due to several factors including the health of society socio-economic level, education, the environment, health and social culture. The research purposed was to determine the relationship of environmental sanitation with the incidence of pulmonary tuberculosis in Hamlet Village Tawangsari Bandarsari District of Ngoro Mojokerto. Corelational analytical study design with cross sectional approach. Whole families in the village population Tawangsari Bandarasri Village District of Ngoro 2015 as many as 89 households and a sample was taken by total sampling as many as 89 families. Data collected by distributing questionnaires and observation records. Having collected the data processing is done and continued with crosstabs. The research found that of the 89 respondents who have a healthy home and did not occur pulmonary TB as many as 69 respondents (77.5%). It can be concluded that there is a relationship of environmental sanitation with pulmonary TB incidence in Hamlet Village Tawangsari Bandarasri District of Ngoro Mojokerto. Respondents are expected to increase knowledge about pulmonary TB and can still maintain a sanitary environment.Keywords: environmental sanitation , pulmonary tuberculosis